Penerapan Hukuman Rehabilitasi Terhadap Pecandu Narkotika (Studi Kasus Putusan Pengadilan Negeri Jakarta Utara Nomor 115/Pid.Sus/2023/PN Jkt. Utr) - Renata, Agnestalia; Myharto, Wiend Sakti (Neolectura, 2024)
The crime of narcotics offenses is considered an extraordinary crime. Law Number 35 of 2009 concerning Narcotics, Article 1 point 13, states that a Narcotics Addict is a person who uses or abuses Narcotics and is in a state of dependency on Narcotics, both physically and psychologically. Narcotic rehabilitation is one of the efforts to save addicts from the shackles of narcotics and the dangers that accompany them. There are three stages of narcotic rehabilitation in Indonesia: medical rehabilitation, non-medical rehabilitation, and advanced rehabilitation. The problem formulation in this study is how the rehabilitation punishment for narcotics addicts is applied and how the analysis of the considerations of the Panel of Judges of the North Jakarta District Court in imposing rehabilitation sanctions in decision number 1151/Pid.Sus/2023/PN Jkt.Utr. The type of research in this legal research proposal is normative legal research, focusing on the applicable legal norms, namely positive legal norms in the form of legislation. The results of the study show that the provisions for rehabilitation for narcotics addicts are stipulated in Articles 54 and 127 of Law Number 35 of 2009 concerning Narcotics. Meanwhile, the classification of user groups is regulated in the Circular of the Supreme Court No. 4 of 2010 concerning the Placement of Abusers, Victims of Abuse, and Narcotics Addicts in Medical and Social Rehabilitation Institutions. The judge's basis for sentencing the Defendant to undergo treatment and/or care at a medical/social rehabilitation institution refers to the provisions of Article 103 jo Article 127 paragraph 2 jo Article 54 of the Republic of Indonesia Law No. 35 of 2009 concerning Narcotics jo Circular of the Supreme Court of the Republic of Indonesia No. 4 of 2010 dated April 7, 2010, concerning the Placement of Abusers, Victims of Abuse, and Narcotics Addicts into Medical and Social Rehabilitation Institutions, as well as other legal facts revealed in the trial.